Novel Role of VisP and the Wzz System during O-Antigen Assembly in Salmonella enterica Serovar Typhimurium Pathogenesis - Silva, Patrick da [UNESP]; Manieri, Fernanda Z. [UNESP]; Herrera, Carmen M.; Trent, M. Stephen; Moreira, Cristiano G. [UNESP] (Amer Soc Microbiology, 2018)
Salmonella enterica serovars are associated with diarrhea and gastroenteritis and are a helpful model for understanding host-pathogen mechanisms. Salmonella enterica serovar Typhimurium regulates the distribution of O antigen (OAg) and presents a trimodal distribution based on Wzy polymerase and the Wzz(ST) (longchain-length OAg [L-OAg]) and Wzz(fepE) (very-long-chain-length OAg [VL-OAg]) copolymerases; however, several mechanisms regulating this process remain unclear. Here, we report that LPS modifications modulate the infectious process and that OAg chain length determination plays an essential role during infection. An increase in VL-OAg is dependent on Wzy polymerase, which is promoted by a growth condition resembling the environment of Salmonella-containing vacuoles (SCVs). The virulence- and stress-related periplasmic protein (VisP) participates in OAg synthesis, as a Delta visP mutant presents a semirough OAg phenotype. The Delta visP mutant has greatly decreased motility and J774 macrophage survival in a colitis model of infection. Interestingly, the phenotype is restored after mutation of the wzz(ST) or Wzz(fepE) gene in a Delta visP background. Loss of both the visP and wzz(ST) genes promotes an imbalance in flagellin secretion. L-OAg may function as a shield against host immune systems in the beginning of an infectious process, and VL-OAg protects bacteria during SCV maturation and facilitates intramacrophage replication. Taken together, these data highlight the roles of OAg length in generating phenotypes during S. Typhimurium pathogenesis and show the periplasmic protein VisP as a novel protein in the OAg biosynthesis pathway.
Keywords: Salmonella; LPS; O antigen; VisP; lipopolysaccharide